Cool and hot executive function in conduct-disordered adolescents with and without co-morbid attention deficit hyperactivity disorder: relationships with externalizing behaviours. Issue 11 (November 2013) - Dolan, M.; Lennox, C.
<x content-type="archive" xml:space="preserve">Abstract</x> Background An understanding of the exact nature of executive function (EF) deficits in conduct disorder (CD) remains elusive because of issues of co-morbidity with attention deficit hyperactivity disorder (ADHD). Method Seventy-two adolescents with CD, 35 with CD + ADHD and 20 healthy controls (HCs) were assessed on a computerized battery of putative 'cool' and 'hot' EFs. Participants also completed the Child Behaviour Checklist (CBCL). Results In the cool EF tasks such as planning, the CD + ADHD group in particular showed most notable impairments compared to HCs. This pattern was less evident for set shifting and behavioural inhibition but there were significant correlations between errors scores on these tasks and indices of externalizing behaviours on the CBCL across the sample. For hot EF tasks, all clinical groups performed worse than HCs on delay of gratification and poor performance was correlated with externalizing scores. Although there were no notable group differences on the punishment-based card-playing task, there were significant correlations between ultimate payout and externalizing behaviour across groups. Conclusions Overall, our findings highlight the fact that there may be more common than distinguishing neuropsychological underpinnings to these co-morbid disorders and that a dimensional symptom-based approach may be the way forward.